Mutation profile and molecular heterogeneity in mismatch repair deficient endometrial carcinoma - Cai, Yumeng; Wang, Jing; Zhang, Zijuan; Li, Pan; Fang, Jiuyuan; Cui, Liang; Xu, Sicong; Zhang, Yuhan; Pang, Junyi; You, Yan; Wu, Huanwen; Liang, Zhiyong (Frontiers in Oncology, 2025)
Endometrial carcinoma (EC) with deficient DNA mismatch repair (dMMR) is a specific molecular entity with unique clinicopathological features. Herein, we depicted the mutation profile of dMMR ECs and explored the molecular heterogeneity among dMMR subgroups with different etiologies. Next-generation sequencing (NGS) based on a 1021-gene panel was applied to 74 dMMR ECs and 43 proficient DNA mismatch repair (pMMR) ECs. In addition, methylation-specific Polymerase Chain Reaction (PCR) was applied for accessing MLH1 promoter hypermethylation (MLH1me+) in dMMR cases. The mutation rates of PTEN, ARID1A, KRAS, and MSH2 were significantly higher in dMMR group, while the CTNNB1 and MSH3 mutations were more commonly observed in pMMR group (p<0.05). Compared to pMMR ECs, dMMR ECs had significantly higher alteration frequencies in WNT, NOTCH, Cell Cycle and MMR, HRR and BER pathway (p<0.05). Remarkably, the interaction patterns within and across pathways were different between dMMR and pMMR groups. Intriguingly, no CTNNB1 mutation were found in dMMR ECs, while half of the WNT-activated pMMR ECs were CTNNB1 mutated, which were generally mutually exclusive with other WNT pathway key genes. The median tumor mutational burden (TMB) of dMMR ECs was significantly higher than pMMR ECs. However, ultra-high TMB value was related to pathogenic POLE mutation both in dMMR and pMMR ECs. As for dMMR subgroups (MLH1me+, Lynch and Lynch-like), KEAP1 and FBXW7 mutations, which may have potential predictive effect of immunotherapy, were enriched in the Lynch subgroup. dMMR ECs has distinctive genomic profile with molecular heterogeneity, which may have potential prognostic and therapeutic implications.